Characterization of the renal cortical transcriptome following Roux-en-Y gastric bypass surgery in experimental diabetic kidney disease. Issue 1 (2nd August 2020) - Nair, Meera; Martin, William P; Zhernovkov, Vadim; Elliott, Jessie A; Fearon, Naomi; Eckhardt, Hans; McCormack, Janet; Godson, Catherine; Brennan, Eoin Patrick; Fandriks, Lars; Docherty, Neil G; le Roux, Carel W
Abstract : Introduction: Roux-en-Y gastric bypass surgery (RYGB) reduces albuminuria and the long-term incidence of end-stage renal disease in patients with obesity and diabetes. Preclinical modeling in experimental diabetic kidney disease demonstrates that improvements in glomerular structure likely underpin these findings. Research design and methods: In adult male Zucker diabetic fatty (ZDF) rats, we profiled the effect of RYGB on weight and metabolic control as well biochemical, structural and ultrastructural indices of diabetic renal injury. Furthermore, we sequenced the renal cortical transcriptome in these rats and used bioinformatic pathway analyses to characterize the transcriptional alterations governing the renal reparative response to RYGB. Results: In parallel with improvements in weight and metabolic control, RYGB reduced albuminuria, glomerulomegaly, podocyte stress and podocyte foot process effacement. Pathway analysis of RYGB-induced transcriptomic changes in the renal cortex highlighted correction of disease-associated alterations in fibrosis, inflammation and biological oxidation pathways. RYGB reversed disease-associated changes in the expression of transforming growth factor (TGF)-β superfamily genes that strongly correlated with improvements in structural measures of glomerulopathy. Conclusions: Improved glomerular structure in ZDF rats following RYGB is underpinned by pathway level changes, including interruption of the TGF-β-driven early profibrotic programme. Our data provide an important layer of experimental support for clinical evidence demonstrating that RYGB arrests renal damage in patients with obesity and type 2 diabetes.